The great philosophers - Stangroom, Jeremy (Capella, 2005)
This accomplished book presents a lucid exposition of the greatest exponents of the various schools of the Western philosophical tradition. It is an invaluable work of reference, both for the advanced student seeking an introduction to the work of an individual philosopher, and to those approaching the subject for the first time.